HISTORICAL AND PEDAGOGICAL ASPECTS OF DEVELOPMENT OF THE NATIONAL PHYSICAL EDUCATION (LAST QUARTER OF XIX – EARLY XX CENTURY) - Cherpak, Yurii V. (Educological discourse, 2015)
On the basis of a broad textual material carried analіz historical and pedagogical aspects of development of the national physical education during the second half of XIX – early XX century. In particular, uncovered views on physical education P. Lesgaft, his supporters A.Anohin and A.Butovsky. Revealed the methods of physical education, developed by Russian scientists in the period under review. It is noted that while gradually going formation and development of the domestic theory and physical education, which absorbed the elements and foreign copyright gymnastic systems and best practices, theoretical and methodological achievements of domestic authors.